2017
DOI: 10.3390/min7070119
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Supported Leaching of Electric Arc Furnace (EAF) Slag by Ammonium Salts

Abstract: Abstract:The effect of microwave-supported leaching of electric arc furnace (EAF) slag by ammonium salts was investigated to improve calcium leaching ratio for CO 2 mineral sequestration process. The results show that the calcium leaching ratio from EAF slag at the constant temperature in the microwave field increases about 10% than that under the water bath at the same leaching time. The greater the microwave power, the higher the impact of calcium leaching rate, which proves that microwave treatment can impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…As in situ heat generation alleviates the heat transfer limitations of the conventional ovens, materials can be processed at a faster rate via the use of the microwave ovens. The properties of in-core volumetric and uniform heating, lower thermal inertia and faster responses make microwave chemistry applied widely [7,8]. In the materials and metallurgy research, microwave assisted synthesis of catalysts, electrodes, and optical devices [9][10][11] have proven to be efficient with some special effects.…”
Section: Introductionmentioning
confidence: 99%
“…As in situ heat generation alleviates the heat transfer limitations of the conventional ovens, materials can be processed at a faster rate via the use of the microwave ovens. The properties of in-core volumetric and uniform heating, lower thermal inertia and faster responses make microwave chemistry applied widely [7,8]. In the materials and metallurgy research, microwave assisted synthesis of catalysts, electrodes, and optical devices [9][10][11] have proven to be efficient with some special effects.…”
Section: Introductionmentioning
confidence: 99%
“…The Ca and Na recovery was evaluated to use potentially the leached solution for aqueous mineral carbonation to sequester CO 2 . Many studies have used an NH 4 Cl solution as a solvent during microwave‐assisted metal leaching processes . However, in this study, solid NH 4 Cl instead of an NH 4 Cl solution was used as a chlorinating agent during the microwave pretreatment of red mud to induce a rapid temperature increase by minimizing heat loss by water.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used an NH 4 Cl solution as a solvent during microwave-assisted metal leaching processes. 23,28,29 However, in this study, solid NH 4 Cl instead of an NH 4 Cl solution was used as a chlorinating agent during the microwave pretreatment of red mud to induce a rapid temperature increase by minimizing heat loss by water. The NH 4 Cl as a chlorinating agent was selected because an NH 4 Cl solution was reported as an effective solvent for aqueous mineral carbonation when the solute is a material with high alkalinity (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finely ground and heat-activated serpentine derived from mining residues has also been studied for CO 2 capture and sequestration 25 . Additionally, some unconventional methods, such as ultrasonic and microwave treatment, have been shown to be effective for leaching 26–28 . Our previous study showed that microwave irradiation can improve the calcium leaching ratio by approximately 10% 28 ; however, the leaching mechanism requires further research.…”
Section: Introductionmentioning
confidence: 99%